TURMAS HETEROGÉNEAS NO ENSINO SUPERIOR:UM DESAFIO PARA O PROFESSOR E PARA O ALUNO - Martins, Maria do Carmo (European Scientific Journal, ESJ, 2014)
This paper presents a case study about teaching Forma e Espaço to a class of students with heterogeneous mathematical background. The course is part of the second semester of the degree in EducaçãoBásica from the University of Azores. The study of teaching heterogeneous classes has been investigated in the past in different education levels: from high school to university.Here we focus on higher education. This problem reached some university courses in the recent past and revealed to be a real challenge both for the teacher and for the students, ending, most of the time, in a disappointing high degree of failures.This research narrates the experience of teaching this course for the past six years; here, we present and discuss the outcome of an inquire made to 36 students about the theoretical and practical subjects taught, as well as the professor‘s performance. We conclude that even though the outcome from the inquire shows promising results, there is still room for improving the methodologies and techniques used for teaching, which we envision that will contribute to diminish the degree of student failures to classes of thiskind.